Analysis of the Financial Performance of the Aceh Besar Regency Government (2019–2024) Based on Local Government Financial Ratios - Fairus Athirah; Agustina (Indonesian Journal Economic Review (IJER), 2026)
This study aims to analyze the financial performance of the Aceh Besar Regency Government for the period 2019–2024 based on local government financial ratios. The research employs a descriptive quantitative method using secondary data in the form of the Realization Report of the Government Budget (LRA) of Aceh Besar Regency, which was obtained through documentation techniques. The analysis utilizes ratios of independence, effectiveness, efficiency, growth, and activity. The research results indicate that the independence ratio is in the very low category, the effectiveness ratio is classified as sufficiently effective, the efficiency ratio falls into the inefficient category, the growth ratio shows fluctuating conditions, and the activity ratio indicates that the allocation of local spending is still dominated by operational expenditures compared to capital expenditures. Therefore, the financial performance of the Aceh Besar Regency Government during the 2019–2024 period is not optimal, particularly in enhancing fiscal independence, budget management efficiency, and balanced allocation of local spending.